Age-Related Differences in Affective Norms for Chinese Words (AANC) - Liu, Pingping; Lu, Qin; Zhang, Zhen; Tang, Jie; Han, Buxin (Frontiers in Psychology, 2021)
Information on age-related differences in affective meanings of words is widely used by researchers to study emotions, word recognition, attention, memory and text-based sentiment analysis. To date, no Chinese affective norms for older adults are available although Chinese as a spoken language has the largest population in the world. This article presents the first large-scale Age-related Affective Norms for 2,061 4-character Chinese words (AANC). Each word in this database has rating values in the four dimensions, namely valence, arousal, dominance, and familiarity. We found that older adults tended to perceive positive words as more arousing and less controllable, and evaluate negative words as less arousing and more controllable than younger adults did. This indicates that the positivity effect is reliable for older adults who show a processing bias toward positive versus negative words. Our AANC database supplies valuable information for researchers to study how emotional characteristics of words influence the cognitive processes, and how this influence evolves with age. This age-related difference study on affective norms not only provides a tool for cognitive science, gerontology, and psychology in experimental studies, but also serves as a valuable resource for affective analysis in various natural language processing applications.